The nonlinear relationship between public debt and Sovereign credit ratings - Hadzi-Vaskov, Metodij (IMF working paper ;, 2019)
This study investigates the nonlinear relationship between public debt and sovereign credit ratings, using a wide sample of over one hundred advanced, emerging, and developing economies. It finds that: i) higher public debt lowers the probability of being placed in a higher rating category; ii) the negative debt-ratings relationship is nonlinear and depends on the rating grade itself; and iii) the identified nonlinearity explains the differential impact of debt on ratings in advanced economies versus in emerging markets and developing economies. These results hold for both gross debt and net debt, and are robust to alternative dependent variable definitions, analytical techniques, and empirical specifications. These findings underscore the potential for fiscal consolidation in helping countries achieve a better credit rating.